Emergence of the colonizer and the colonized in three texts: William Shakespeare's the tempest , Aphra Behn's Oroonoko: or, the royal slave and Daniel Defoe's Robinson Crusoe - Nehar, Nowshin (BRAC University, 2010)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2006.